Hyaluronic acid for periodontal tissue regeneration in intrabony defects. A systematic review. - Manuel Rodríguez-Aranda; Iris Iborra-Badia; Francisco Alpiste-Illueca; Andrés López-Roldán (Elsevier, 2022)
Objective: To evaluate the clinical and radiographic outcomes of hyaluronic acid (HA) application alone and in combination with other therapies for the surgical treatment of periodontal intrabony defects. Material and methods: This review was designed in accordance with the PRISMA (preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement based on the proposed focused question. A literature review with no restrictions regarding the status or language of publication was performed until June 2022. Randomised clinical trials, controlled clinical trials, case series, and case reports were considered eligible for inclusion. The Cochrane risk of bias tool was used to assess the methodology of the included studies. The use of HA was divided into four categories depending on whether it was a) applied alone, b) in combination with barriers, c) in combination with growth factors, or d) in combination with bone grafts. Results: Nine studies were included in the analysis. Some of the studies presented variable heterogeneity and a high risk of bias. Every group resulted in a statistically significant improvement in clinical attachment level (CAL) and probing pocket depth after 6-12 months of follow-up. Three studies showed significant results for bone defect filling on using HA. Conclusion: The application of HA can provide moderate and beneficial clinical and radiographic results for the surgical treatment of periodontal regeneration. The heterogeneity and high risk of bias of the included studies reveal the need to perform randomised clinical trials with an appropriate methodological design to evaluate the effect of HA in periodontal regeneration.